Impact of Antibiotic and Heavy Metals Sensitivity on Oral Isolate: A case study - Makky, Essam A.; Ali, Muna Jalal; M. M., Yusoff (JOCPR, 2015)
Tooth decay are considered the most common in the world. The study aims to isolation and identification of important bacteria related to tooth decay, determining the sensitivity of bacteria of certain types of antimicrobial agents and studying the effect of heavy metals on bacterial isolates. A total (50) swabs were collected from mouths of patients from both gender and their ages range from 1-60 years which are referred to consult the dental clinics and specialized centers, in order to isolate and identify the causative agents that associated with oral diseases. The age stage group of infection rates showed groups (20-40) and (1-20) were the most infected compared to elder group (40-60) as was the incidence of 44and 32% respectively The antibiotic sensitivity test against the isolates showed the chloramphenicol up to 83.05% was the higher effect sensitivity of Gentamicin and Rifampicin up to 81.35% .While streptomycin 16.94% and penicillin G 64.40%. Also, these differences were found have lower effect for isolates against (7) heavy metals, where it showed resistance to Silver nitrate, Iron chloride, Zinc chloride, lead acetate to100%, while appeared sensitivity to mercury, cadmium and copper sulfate by 100,86.44and 1.69% respectively.